The early twentieth century´s print advertising. Analysis of the advertisements published in "La Voz de Galicia" since 1900 to 1920 - Feijoo Fernández, Beatriz; Fernández Vázquez, Jessica (Historia y Comunicación Social, 2014)
The early years of 20th century pushed the Spanish press to a lot of changes. The newspapers were able of overcoming their ideological function to get a new business interest with the main objective of maintaining the citizens alright informed. In this way, the press needed external resources to keep its operation and consequently, the advertisement became one of the most important financial supports, whose function takes place until nowadays. In relation with this, we would like to emphasize the Galician diary La Voz de Galicia, whose labor stand out among other diaries in that period. It is a commercial diary, it needs to publish announcements in their pages, and thus it could be interesting to study the level of penetration of the advertisements in this newspaper in addition to the main announcers in these early years of 20th Century.